Intercalary frozen autografts for reconstruction of bone defects following meta-/diaphyseal tumor resection at the extremities - Jingyan Yang; Wenze Li; Rongjie Feng; Dong Li (BMC Musculoskeletal Disorders, 2022)
Abstract Background For patients with malignant limb tumors, salvage surgery can be achieved using endoprosthesis or biological reconstructions like allograft or autograft. In carefully selected patients, resected bone can be recycled after sterilization using methods like autoclaving, irradiation, pasteurization or freezing with liquid nitrogen. We evaluated the clinical outcome and complications of malignant limb tumors treated with intercalary resection and frozen autograft reconstruction. Methods We reviewed 33 patients whose malignant bone tumors were treated by wide resection and reconstruction with recycling liquid nitrogen-treated autografts between 2006 and 2017. Limb function, bone union at the osteotomy site and complications were evaluated. Functional outcome was assessed using the Musculoskeletal Tumor Society (MSTS) scoring system. Results The cohort comprised 16 males and 17 females, with a mean age of 35.4 years (14–76 years). The most common tumor was osteosarcoma (7 cases). Tumors were located in the humerus (5), ulna (1), femur (10) and tibia (17). The mean follow-up was 49.9 months (range 12–127 months). Of the 33 patients, 16 remained disease-free, and 3 were alive with disease. The mean size of the defect after tumor resection was 11.6 cm (range 6–25 cm). Bone union was achieved in 32 patients, with a mean union time of 8.8 months (range 4–18 months). Complications included 1 graft nonunion, 2 infections (1 superficial, 1 deep infection), 1 leg length discrepancy, 2 graft fractures and 3 local recurrences. The mean MSTS score was 87.2% (range 70–100%). Conclusion Liquid nitrogen-treated tumor-bearing autograft is an effective option for biological reconstruction after meta-/diaphyseal tumor resection of long bones. This method has excellent clinical outcomes and is especially recommended for patients with no severe osteolytic bone tumors.